Endocrine cell micronests in an ovarian mucinous borderline tumor: a potential diagnostic pitfall for microinvasion - Katrina Collins; Sheila Segura; Michael Hwang (BMC, 2022)
Abstract The occurrence of endocrine cell micronests in ovarian tumors is rarely reported. To our knowledge, there are only three prior cases reported to date: one occurring in an ovarian mucinous cystadenoma, one in an ovarian mucinous cystadenofibroma, and another in an ovarian mucinous carcinoma with a predominant borderline component. This is a 27-year-old woman that presented with a one-month history of abdominal pain and fullness. Imaging studies revealed a large multiloculated cystic and solid mass measuring 23 cm occupying the majority of the pelvis and abdomen concerning for a primary ovarian malignancy. The patient underwent a right salpingo-oophorectomy with appendectomy. Histologic sections from the ovary showed a multiloculated, cystic and focally solid mass lined by gastrointestinal-type mucinous epithelium with variable degrees of proliferation accounting for greater than 10% of the tumor. In addition to the mucinous epithelial component, there were several foci of bland, monotonous epithelioid cells arranged in solid nests with focal tubular/acinar formation within the fibrous septa and mucinous epithelium. Immunohistochemical studies showed that these cells were positive for cytokeratin, EMA, and synaptophysin, while negative for inhibin. The Ki-67 proliferation index was low (<1%). The presence of endocrine cell nests associated with an ovarian mucinous neoplasm is a rare phenomenon. Whether this represents preservation of endocrine cells in the context of epithelial degeneration or an independent neoplastic component is unclear. Progression related to this endocrine cell proliferation is unlikely and the recognition of this phenomenon holds more diagnostic value than prognostic significance, as it could be confused with microinvasion or sex cord stromal elements.